Higher cardiac vagal activity predicts lower peripheral resistance 6 years later in European but not African Americans - Williams, DeWayne P. (Am J Physiol Heart Circ Physiol, 2021)
African American (AA) individuals are at a greater risk for the development of cardiovascular complications, such as hypertension, compared with European Americans (EAs). Higher vagally mediated heart rate variability (HRV) is typically associated with lower blood pressure (BP) and total peripheral resistance (TPR). However, research has yet to examine the differential impact of HRV on longitudinal hemodynamic activity between AAs and EAs. We sought to rectify this in a sample of 385 normotensive youths (207 AAs, 178 EAs; mean age 23.16 ± 2.9 yr). Individuals participated in two laboratory evaluations spanning approximately 6 yr. Bioimpedance was used to assess HRV at time 1 and cardiac output at both time 1 and time 2. Mean arterial pressure (MAP) was measured at both time points via an automated BP machine. TPR was calculated as MAP divided by cardiac output. Results showed AAs to have higher BP and higher TPR at time 2 compared with EAs, independent of several important covariates. Also, higher HRV at time 1 significantly predicted both lower TPR and BP at time 2 among EAs only; these associations were attenuated and not significant in AAs. HRV did not significantly predict cardiac output at time 2 in the full sample or split by ethnicity. Our findings highlight that AAs show TPR mediated long-term increases in BP irrespective of resting HRV, providing a physiological pathway linking AAs with a greater risk for mortality and morbidity from hypertension and potentially other cardiovascular disease. NEW & NEWSWORTHY African Americans and European Americans differ in hemodynamics underlying long-term blood pressure regulation. Over 6 yr, African Americans show total peripheral resistance-mediated increases in blood pressure compared with European Americans. Higher heart rate variability predicts lower blood pressure and total peripheral resistance 6 yr later in European Americans but not African Americans.